2015
DOI: 10.18632/oncotarget.4507
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial high-throughput experimental and bioinformatic approach identifies molecular pathways linked with the sensitivity to anticancer target drugs

Abstract: Effective choice of anticancer drugs is important problem of modern medicine. We developed a method termed OncoFinder for the analysis of new type of biomarkers reflecting activation of intracellular signaling and metabolic molecular pathways. These biomarkers may be linked with the sensitivity to anticancer drugs. In this study, we compared the experimental data obtained in our laboratory and in the Genomics of Drug Sensitivity in Cancer (GDS) project for testing response to anticancer drugs and transcriptome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…The IC50 values of sunitinib has been reported as 6 µM 37) and 2.3 µM 38) in Jurkat cells, whereas the IC50 values of compound 3f was 7.8 µM in Jurkat cells in this study. The structural comparison between compound 3f and sunitinib revealed that the compound 3f is very much structurally related to sunitinib, as both of the compounds share fluorine as their moiety in isatin ring (Figure 10) which might be center for the functional activity of these two compounds.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationcontrasting
confidence: 51%
“…The IC50 values of sunitinib has been reported as 6 µM 37) and 2.3 µM 38) in Jurkat cells, whereas the IC50 values of compound 3f was 7.8 µM in Jurkat cells in this study. The structural comparison between compound 3f and sunitinib revealed that the compound 3f is very much structurally related to sunitinib, as both of the compounds share fluorine as their moiety in isatin ring (Figure 10) which might be center for the functional activity of these two compounds.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationcontrasting
confidence: 51%
“…Previous work has focussed on developing predictive models using drug-sensitivity data from cell lines373839. MiSL provides an alternate synthetic lethality-based approach to identify predictive biomarkers for targeted therapies.…”
Section: Resultsmentioning
confidence: 99%
“…The enclosed algorithm operates with the so-called Pathway Activation Strength value, which is a qualitative characteristic of pathway activity in a cancer sample. This approach was used to identify molecular features accounting for the tumor response to target drugs in cell-based models [69] and patients [70]. In glioblastoma, 59 abnormally regulated intracellular signaling pathways could be revealed by Oncofinder [71].…”
Section: Personalized Medicine Paradigm For the Treatment Of Brain Tumentioning
confidence: 99%